Features and Problems of Attracting Investments into Agriculture of Kazakhstan - OMARKHANOVA, Zhibek; TLEUZHANOVA, Danagul; BERSTEMBAYEVA, Rysty; MUKHAMBETOVA, Zamira; MATAYEVA, Botagoz; ALINA, Gulzhan (Journal of Advanced Research in Law and Economics; Vol 8 No 4(26) (2017): JARLE Volume 8 Issue 4(26) Summer 2017, 2017)
In the article made the analysis of investment in agriculture, also mentioned the conclusion that the positive dynamics in the development of agricultural production, observed changes, and quality of character. Considered the peculiarities of capital investments in agriculture and analyzed the current state of the investment potential of agriculture of the Republic of Kazakhstan. Analyzed the composition and structure of sources of investments into fixed capital of agriculture. The necessity of increasing the volume of investments in modernization of fixed assets in agriculture.